Trickle irrigation systems affect spatial distribution of roots of banana crop - Edvaldo B. Santana Junior; Eugênio F. Coelho; Jailson L. Cruz; João B. R. da S. Reis; Diego M. de Mello; Bruno L. da S. Pereira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Trickle irrigation has been largely used for banana in Brazil, mainly due to the increase in water and fertilizer use efficiency. These irrigation systems have different options concerning number, type and flow rate of emitters as well as for hydraulics, number and location of lateral lines. The small area of soil wetted by these systems limits root spatial distribution of crops. This study aimed to evaluate the effect of different trickle irrigation systems on the root spatial growth and root spatial distribution of banana cv. Prata Gorutuba. Root length density and root length were evaluated in soil profiles of three micro-sprinkler systems, with emitter flow rates of 35, 53 and 70 L h-1 and of two drip irrigation systems, with one and two lateral lines per crop row. Trickle irrigation systems influence root spatial distribution, favoring a greater or smaller distribution of roots at different depth and distance from the plant according to micro-sprinkler flow rate and to the number of lateral lines per crop row. The effect on root spatial distribution is more accentuated for micro-sprinkler systems than for drip systems. The majority of the total root length (80%) was observed in the soil profiles from 0.33 to 0.57 m depth and at distances from the plants of 0.75 to 0.83 m.